Mineral composition of the red currant (Ribes rubrum L.) variety Redpoll lyophilized waste extract - Cvetković, Maja; Ilić, Dušan; Petrović, Sanja; Miladinović, Bojana (Archives of Pharmacy, 2022)
Red currants are berries appreciated for their characteristic aroma, trendy shape and numerous health benefits. They are abundant in sugars and phytonutrients. Red currants are also an excellent source of minerals. According to the literature, red currants are especially rich in potassium, calcium and magnesium. The aim of this study was to determine the contents of mineral elements in lyophilized waste extract obtained from red currant variety Redpoll (Ribes rubrum L.), in order to evaluate its possible applications. The analysis included the determination of 22 chemical elements. Sample preparation was performed by wet digestion, after which the concentration of elements was determined by inductively coupled plasma - optical emission spectrometry (ICP-OES). The mineral composition is shown by decreasing concentrations: K<P<<S<Mg<Ca<Na<Ba<Zn<Sr<Cu<Fe<Si<Mn<Ni<Li. Minerals as Ag, As, Cd, Co, Cr, Pb, and Ti were not detected in the sample. Minerals that are in the highest concentration (K (25,37 mg/g), P (9,482 mg/g), Mg (0.724 mg/g) , Ca (0.637 mg/g)) have many benefits. High intake of K, Mg and Ca is associated with a reduced risk of stroke, hypertension and osteoporosis. Iron is an essential part of many compounds in the oxygen transport and function as cofactors for enzymes. The toxic metals weren’t isolated, so do not pose any health risk. The data obtained in this study show that Redpoll waste represents valuable source of minerals that can be used in human nutrition and food industry.